The Impact of Problem Based Learning Model for the Result of Social Subject Grade VIII in SMP Cinta Rakyat 3 Pematang Siantar Year 2022/2023 - Destiana br Panjaitan; Tumpal Manahara Siahaan; Anton Luvi Siahaan (International Journal of Integrated Science and Technology, 2023)
The problem in this research is the low economic learning outcomes of students in the learning process. This research aims to determine the effect of the problem based learning model on the social studies learning outcomes of class VIII students at Cinta Rakyat 3 Private Middle School Pematang Siantar FY 2022/2023. The research used a quasi-experimental method with a Noneqivalent Control Group Design. This design consists of two stages, namely pretest and posttest. The sample in the research in class VIII-C was 32 students and VIII-D was 32 students. The research instrument used was the learning outcomes test. From the results of the analysis carried out in the experimental class, the average pretest score was 47.34 and posttest was 73.91. Meanwhile, in the control class the average pretest score was 38.59 and the average posttest score was 53.12. The results of hypothesis testing using the independent sample t-test obtained tcount 4.706 > ttable 1.295 and the significance was 0.000 <0.005 so it can be concluded that the learning outcomes of students taught using the problem based learning model are influential and good for use in learning.